Kak samoocenka i trevožnost' sootnosjatsja s uspešnost'ju v sportivnoj dejatel'nosti - Evseev, A. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The relationship between the need to achieve performance and the level of anxiety was revealed. A number of correlations between the emotional manifestations and anxiety of athletes are determined: among the athletes with a high level of the personal anxiety, the intensity of the emotion of "joy" is extremely low, and the emotions of "fear" and "anger" dominate in their nonverbal manifestations. Positive correlations are tracked between emotional manifestations of " joy" with test indicators of "strength" and "endurance", and the emotion "fear" is negatively correlated with test indicators of power and speed-power manifestations. Effective ways to regulate reactive anxiety is to vary the subjective significance of the event, as well as the use of methods of psychological correction.